Increasing cefazolin use for surgical prophylaxis in penicillin-allergy-labeled patients - Kathryn A. VanderVelde; Sarah L. Suppes; Katherine A. Gibbs; Kevin H. Latz; Angela C. Vanderpool; Rana E. El Feghaly; Jennifer L. Goldman (Cambridge University Press, 2023)
Abstract Objective: Penicillin (PCN) allergy labels affect antimicrobial selection for surgical prophylaxis. We aimed to increase the percentage of cefazolin usage in patients with PCN allergy labels undergoing orthopedic surgery from 50% to 80%. Design: Quality improvement initiative. Setting: Children's Mercy Kansas City (CMKC), a freestanding children's hospital. Patients: Children scheduled for an orthopedic surgery (excluding spinal surgery) at CMKC who had a PCN allergy label and received a perioperative antibiotic. Methods: No standardized process existed to identify and clarify PCN-allergic-labeled patients preoperatively. We developed a process for patient identification combined with a pharmacist phone interview for PCN allergy clarification. In plan-do-study-act (PDSA) part 1, we implemented a computer-generated patient list. In PDSA part 2, we combined automated identification with a phone interview. In PDSA part 3, we enhanced the patient list, making it timely and concise. In PDSA part 4, we included a PCN allergy clarification electronic survey to caregivers via the electronic medical record. Results: Cefazolin use in PCN-allergic surgical patients increased from 50% to 74% following interventions. Patients who had their PCN allergy label clarified were 4 times more likely to receive cefazolin compared to those whose allergy labels were not clarified (OR, 4.21; 95% CI, 1.68-11.61; P = 0.003). Moreover, 90% of patients received cefazolin when their PCN allergy was clarified and cefazolin was recommended. When a PCN allergy label was not clarified, only 59% of patients received cefazolin. Conclusions: Appropriate clarification and documentation of PCN allergy labels increases the use of cefazolin for surgical prophylaxis.